Low Complexity High-Performance Precoding Algorithms for mm-Wave MU-MIMO Communication System - El-abd, Rania H.; Abdullah, Haythem H.; Elazim, Mohamed Abd; Samrah, Ahmed sh (Wireless personal communications, 2020)
In this paper, linear precoding (LP) algorithm has been studied to improve the bit error rate (BER) performance of large scale multiple input multiple output (MIMO) system. A new technique of enhancing the BER performance of linear precoding algorithm without complexity in hardware and mathematical calculations is proposed and it is used on a traditional LP algorithms like a Maximum Ratio Transmission (MRT), a Zero-Forcing (ZF), a Regularized Zero-Forcing (RZF), and a Minimum Mean Square Error (MMSE) for Millimeter wave MU-MIMO communication system. A new technique is also used to mitigate the BER gab problem between (ZF, MMSE) and (RZF, MMSE) linear precoding algorithms. The result shows that with using the new technique, the BER performance of modified LP significantly outperform their traditional LP by 10 −5 when using 4 element of BS antenna, 10 −6 when using 16 element of BS antenna and mitigate the BER gab problem at different signal to noise ratio (SNR).